Psychophysical Evaluation of Sensory Reweighting in Bilateral Vestibulopathy - Medendorp, W. Pieter; Alberts, Bart B. G. T.; Verhagen, Wim I. M.; Koppen, Mathieu; Selen, Luc P. J. (Frontiers in Neurology, 2018)
Perception of spatial orientation is thought to rely on the brain’s integration of visual, vestibular, proprioceptive and somatosensory signals, as well as internal beliefs. When one of these signals breaks down, such as the vestibular signal in bilateral vestibulopathy, patients start compensating by relying more on the remaining cues. How these signals are reweighted in this integration process is difficult to establish since they cannot be measured in isolation during natural tasks, are inherently noisy, and can be ambiguous or in conflict. Here, we review our recent work, combining experimental psychophysics with a reverse engineering approach, based on Bayesian inference principles, to quantify sensory noise levels and optimal (re)weighting at the individual subject level, in both patients with bilateral vestibular deficits and healthy controls. We show that these patients reweight the remaining sensory information, relying more on visual and other non-vestibular information than healthy controls in the perception of spatial orientation. This quantification approach could improve diagnostics and prognostics of multisensory integration deficits in vestibular patients, and contribute to an evaluation of rehabilitation therapies directed towards specific training programs.